Efficiency of Inorganic Fertilizer Utilization with Biofertilizer on the Growth and Production of Soybeans (Glycine max (L). Merrill.) - Rahmayuni, Erlina; Herman, Welly; Putri, Elsa Lolita; Mayangsari; Elfarisna (BPFP Universitas Bengkulu, 2023)
Soybeans (Glycine max (L). Merrill.) are an important source of protein in Indonesia whose supply is still very low. One of the causes is low soil fertility so it needs to be fertilized. Continuous fertilization using inorganic fertilizers turns out to have a sustainable effect, namely increasing soil damage, so it needs to be made more efficient with biological fertilizers. The research aims to determine the response of soybean plants to the application of biological fertilizer as an efficient use of inorganics. The research was carried out in Lengkong Poncol Village RT/RW 001/011 Wetan, Serpong District, South Tangerang at an altitude of ± 25 m above sea level from January 2020 to April 2020. The research used a randomized complete group design (RKLT) with five treatments, as follows: NPK 100%, NPK 75% + Biofertilizer 100 ml, NPK 50% + Biofertilizer 100 ml, NPK 25% + Biofertilizer 100 ml, and Biofertilizer 100 ml. Observations were made on plant growth and soil analysis. The results of the research showed that the use of biological fertilizer to make the use of NPK fertilizer more efficient did not have a real effect on plant growth. It can be seen that the use of biological fertilizer by making NPK fertilizer more efficient gave the same results as using 100% NPK fertilizer and using 75% NPK fertilizer + fertilizer. biological 100 ml/plant affects plant height, pH value, and soil nitrogen content.